Seminal human papillomavirus originates from the body surface and is not a frequent aetiological factor in azoospermia. (22nd November 2018) - Fedder, Jens; Ørnskov, Dorthe; Engvad, Birte; Kristensen, Thomas Kielsgaard; Lomholt, Mads; Marcussen, Niels; Waldström, Marianne
Abstract: Human papillomavirus (HPV) DNA has been detected in the testis tissue of 6.5% of 185 men with non‐obstructive azoospermia (NOA). Others have suggested that seminal HPV originates from contamination from the genital skin and mucosa. One hundred unselected azoospermic men and 43 normal men undergoing vasectomy were recruited. Testicular biopsies for HPV examination were collected from all the men. Additionally, the normal men undergoing vasectomy delivered a semen sample and had a swab for HPV examination taken from the genital skin before vasectomy. A piece of each Vas deferens obtained during the vasectomy was examined for the presence of HPV. Two of the primarily azoospermic men were shown to have cryptozoospermia. It was not possible to detect HPV in the testis tissue of any of the included 98 azoospermic men or the 43 proven fertile men. In the proven fertile men, HPV DNA was detected in the semen of 15 men (35%), on the genital skin of 28 men (65%), and in the Vas deferens in three cases (7%). In 13 (87%) men with HPV‐positive semen samples, HPV DNA was also detected in the skin swabs, and in 11 men (73%), identical HPV genotypes were found in the two locations.